Význam vzdelávania vo výkone trestu odňatia slobody - Španková, Jana; Grenčíková, Adriana (Univerzita Pardubice, 2012)
Education is a vital tool for the integration of people at work Under the conditions of the prison system deals with an important means of treatment. It is a psychological factor in its impact on the objective conditions for the new qualifications for security and thereby increase their level of education. So the conditions for successful integration into society increases after release from prison.
The importance of education in conditions of imprisonment
Keywords: training; penitentiary care; integration; people in prisons; punishment; education of convicted